STUDI PERMINTAAN MANISAN RUMPUT LAUT DI KELURAHAN BONTANG KUALA KECAMATAN BONTANG UTARA KOTA BONTANG - Alia Ruaida; Dayang Diah Fidhiani; Qoriah Saleha (2339-1324, 2015)
This study aims to identify factors influencing the demand of candied seaweed in Bontang Kuala Village, North Bontang District, Bontang City and identify the range of price and revenue elasticities from the demand of seaweed candied in Bontang Kuala Village.This study was carried out for one month in April-August 2014 at Bontang Kuala Village. The population from this study was candied seaweed’s buyers. The samples were based from 30 respondents were chosen by accidental sampling.method. Data analysis was used descriptive analysis, multiple linear regression analysis, price elasticity analysis, and revenue elasticity. Results can be concluded that when the price was decreased, the demand of candied seaweed was increased. The elasticity of price from demand of candied seaweed has the value of -5.03>1. Meanwhile, the elasticity of revenue from demand of candied seaweed has the value of (0.17<1).